Predictions of Financial Distress in Consumption Goods Industrial Companies Listed on the Indonesia Stock Exchange in 2016-2018 - Mubarrok, Muhammad Khusni; Wasil, Mohammad; Dharmani, I. G. A. Aju Nitya (Quantitative Economics and Management Studies, 2020)
This study aims to determine the prediction of financial distress in the Consumer Goods Industry companies listed on the Indonesia Stock Exchange. The research period used was 2016-2018. This research on financial distress prediction uses a quantitative approach. The study population includes all Consumer Goods Industry companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The sample is determined by purposive sampling technique. The data analysis method used is logistic regression analysis. This study aims to test and prove whether DAR, CR, TATO, and ROA affect Financial Distress. The data in this study came from secondary data obtained through documentation techniques. Data analysis by logistic regression partially used SPSS for window version 25. The results showed that (1) debt asset to ratio (DAR) had no positive effect on financial distress, (2) current ratio (CR) has a negative but not significant effect on financial distress, (3) total asset turnover (TATO) has no negative effect on financial distress, (4) return on assets (ROA) has a negative and significant effect on financial distress.